ANALISIS MANAJEMEN LOGISTIK OBAT DI INSTALASI FARMASI DINAS KESEHATAN KABUPATEN DEMAK - Muhamad Syaiful Bachri Al Yunus; Chatila Maharani (Jurnal Kesehatan Masyarakat, 2022)
Proper drug logistics management is one of the factors so that drugs can be managed properly. Pharmacy Unit of the Demak District Health Office had problems that were human resources,shortage, obstacles for using the SIMDIO (information system of the Demak District Health Office for systematic recording and reporting) application system, drug storage discrepancy with regulations, etc. The purpose of this study was to determine the analysis of drug logistics management in the pharmaceutical installation of the Demak District Health Office. The research used qualitative methods through in-depth interviews, observations, and observation guides for data collection. The result showed that in planning phase us a combination method (a combination of consumption and epidemiological methods), drug procurement used e-purchasing and e-catalogue systems, good drug receipts because the inspections were carried out, a less spacious building for the drug storage.In addition, sometimes there were delay distribution and inadequate transportation, the drugs` elimination step was not in accordance with regulations. Furthermore, the recording and reporting step was done systematically using the SIMDIO application. For the output aspect, there was unavailability and inadequacy of drugs at the puskesmas. Suggestions for the Demak District Health Office are to carry out routine evaluations of drug logistics management, completing transportation based on regulations, and expanding drug storage warehouses.